California County Planning Association Central District Meeting at Carmel Holiday Inn - Watkins, Howard::::::::: (1984)
David Hendrick (Central Director-Monterey) welcoming everyone; seated speakers Robert Slimmon, Jr. (Monterey County Planning Director) and Brian Finegan (land use attorney) Topic: "How to be a Planning Commissioner"